The Effects of Coir Fibers on Workability and Strength Properties of Concrete - Ghulam Shabir Solangi Solangi; Gulmir Khan Sahito Sahito; Manthar Ali Keerio Keerio (Neutron, 2021)
This study aimed toward analyzing length and content of coir fiber on workability and strength of concrete. For this purpose, different fractions of coir fibers of length as 10 mm, 20 mm and 30mm are used with varying proportions as 0.15%, 20%,0.25%,0.3% and 0.35% by the volume of concrete. One mix of control concrete and 15 mixes of concrete with inclusion of cot fibers were prepared. The experiments were conducted to check the workability, compressive and tensile strength of concrete. It was observed from conducted research, that the workability is decreased with increasing the content of coir fibers. On the basis of conducted research, the inclusion of 0.25% of coir fibers of length 20mm is optimum. With inclusion of 0.25% of coir fibers of length 20mm, compressive and tensile strength is improved as compared to control mix.